Homozygous XYLT2 variants as a cause of spondyloocular syndrome. Issue 4 (20th February 2018) - Umair, M.; Eckstein, G.; Rudolph, G.; Strom, T.; Graf, E.; Hendig, D.; Hoover, J.; Alanay, J.; Meitinger, T.; Schmidt, H.; Ahmad, W.
Abstract : Spondyloocular syndrome (SOS) is a rare autosomal recessive, skeletal disorder. Two recent studies have shown that it is the result of biallelic sequence variants in the XYLT2 gene with pleiotropic effects in multiple organs, including retina, heart muscle, inner ear, cartilage, and bone. The XYLT2 gene encodes xylosyltransferase 2, which catalyzes the transfer of xylose (monosaccharide) to the core protein of proteoglycans (PGs) leading to initiating the process of PG assembly. SOS was originally characterized in 2 families A and B of Iraqi and Turkish origin, respectively. Using DNA from affected members of the same 2 families, we performed whole exome sequencing, which revealed 2 novel homozygous missense variants (c.1159C > T, p.Arg387Trp) and (c.2548G > C, p.Asp850His). Our findings extend the body of evidence that SOS is caused by homozygous variants in the XYLT2 gene. In addition, this report has extended the phenotypic description of SOS by adding follow‐up data from 5 affected individuals in one of the two families, presented here. Abstract : Sequence variants in the XYLT2 gene